How Green Marketing Affects Brand Equity On Wuling Electric Cars: A Study on Gen Z And Millennials - Aldino, Rizki Muhammad; R Indika, Deru (Universitas Negeri Yogyakarta, 2025)
Climate change and carbon emission pollution have made people switch to using environmentally friendly products such as electric cars. Electric car manufacturers must be able to compete with consumer behavior, which has begun to realize the importance of protecting the environment, and must be able to market their products with their environmentally friendly messages. So, Brand Equity is important for electric car manufacturers to compete in the market. This research aims to discover how Green Marketing influences the Brand Equity of Wuling electric cars among Gen Z and Millennials in Bandung. The method used in this study uses a descriptive verification method and a quantitative approach with a questionnaire distributed to 200 respondents via Google Forms, consisting of Gen Z and Millennials in the city of Bandung. In this study, the data were processed and analyzed with PLS-SEM software to see how the influence of variable X, which is Green Marketing, on variable Y, which is Brand Equity. The research results indicate that the Green Marketing strategies have a positive and significant impact on the Brand Equity of Wuling electric cars.